Ambivalence in rehabilitation: thematic analysis of the experiences of lower limb amputated veterans. Issue 21 (9th October 2018) - Christensen, Jan; Langberg, Henning; Doherty, Patrick; Egerod, Ingrid
Abstract: Background: Knowledge about the organization and factors of importance to rehabilitation of veterans with lower limb amputation is sparse. The aim of this study was, therefore, to improve understanding of the influences of "military identity" on the organization of rehabilitation services and to investigate those factors influential in achieving successful rehabilitation, including interprofessional collaboration between different sectors involved in the rehabilitation of veterans with lower limb amputations. Methods: We used a qualitative exploratory design, triangulating interviews and participant observation. Data were generated using in-depth semi-structured interviews ( n = 6) exploring in-hospital and post-hospital rehabilitation in Danish veterans after unilateral lower limb amputation due to trauma. We conducted four sessions of participant observation, during weekly post-hospitalization rehabilitation and included field notes in the dataset. Results: Two main themes emerged: "experiencing different identities" and "experiencing discontinuity in rehabilitation." The first theme illustrated how veterans actively shift between the identities of disabled person, wounded veteran and athlete according to the context. The second theme illustrated the frustration of negotiating military versus civilian mindsets during rehabilitation and lack of coordination between the public healthcare system, municipal services and the military. Conclusion: Veterans live with shifting identities after returning to civilian life, increasing their awareness of the transition from active service to a new life as a civilian. During rehabilitation, it is important to acknowledge the disparities between the military and civilian mindsets and to integrate the different sets of values, such as structure versus autonomy. IMPLICATIONS FOR REHABILITATION: Recommendations for the improvement of rehabilitation of amputated veterans include: Rehabilitation professionals working with veterans should focus on abilities instead of disabilities, in order to support their active identity. Rehabilitation professionals working with veterans should understand and integrate military key components, such as autonomy, structure, clear expectations, goal setting and ongoing testing and adjustment of goals. Rehabilitation professionals working with veterans should facilitate collaboration between civilian and military rehabilitation services, in order to secure both physical and psychosocial reintegration.